Curriculum Management in Achieving School Scope Educational Goals - Hafidin Nurhadi; Hadiansah Hadiansah; Mohamad Erihadiana; Muhibbin Syah (Laboratorium Jurusan S1 Manajemen Pendidikan Islam, 2024)
The curriculum is one of the important tools that determine the success of achieving educational goals in schools. The achievement of educational goals implemented in the application of the right curriculum depends on good curriculum management. This study aims to describe and analyze the implementation of curriculum management at SMPIT Assyifa Boarding School Wanareja Subang in an effort to achieve institutional goals. This research uses a qualitative approach with the type of field research. The results of this study indicate that: 1) The Educational Objective of SMPIT Assyifa Boarding School Wanareja Subang is